Assessment of Knowledge, Attitude, and Practice of Security and Safety Workers Toward the COVID-19 Pandemic: A Cross-Sectional Study - AlRasheed, Maha M.; Alsugair, Abdullah M.; Almarzouqi, Hala F.; Alonazi, Gadah K.; Aleanizy, Fadilah S.; Alqahtani, Fulwah Y.; Shazly, Gamal A.; Khurshid, Fowad (Frontiers in Public Health, 2021)
Aim This study aimed to assess the knowledge, attitudes and practices (KAP) of security and safety workers towards the COVID-19 pandemic in Saudi Arabia. Methods A cross-sectional survey was conducted between April and July 2020 using a self-developed structured questionnaire that was randomly distributed online among security and safety employees in government or private sectors. Results Among 712 participants, 53.9% were female and the respondents mean age was 39.43 years. Television was chosen as the most reliable source of information by 75.0% of the participants. Most respondents had sufficient knowledge about the COVID-19 pandemic, as the majority of them answered the knowledge questions correctly. The significant predictors for their knowledge were their educational level, age, marital status, parenthood status and employment sector (private or government). Our study revealed an overall 98.6% positive attitude of safety and security workers towards COVID-19. Majority of the respondents were following good and safe COVID-19 prevention practices. Conclusion High level of knowledge was reflected in both the attitude and practice of the participants towards the COVID-19 pandemic.